Borrow now, pay even later: A quantitative analysis of student debt payment plans - Michael Boutros; Nuno Clara; Francisco J. Gomes (Bank of Canada, 2023)
In the United States, student debt currently represents the second largest component of consumer debt, just after mortgage loans. Repayment of those loans reduces disposable income early in the borrower's lifecycle, when marginal utility is particularly high, and limits their ability to build a buffer stock of wealth to insure against background risks. In this paper, we study alternative student debt contracts that offer a 10-year deferral period. Borrowers defer either principal payments only ("Principal Payment Deferral", PPD) or all payments ("Full Payment Deferral", FPD) with the missed interest payments added to the value of the debt outstanding. We first calibrate an equilibrium with the current contracts, and then solve for counterfactual equilibria with the PPD or FPD contracts. We find that both alternatives generate economically large welfare gains, which are robust to different assumptions about the behavior of the lenders and borrower preferences. We decompose the gains into the percentages resulting from loan repricing and from the deferral of debt repayments. We compare these alternative contracts with the changes to Income Driven Repayment Plans being proposed by the current U.S. administration and show that they dominate such proposals. Crucially, the PPD and FPD contracts deliver similar welfare gains to the debt relief program considered by the administration, with no impact on the government budget constraint.
Keywords: E2; G5; H3; 330; Asset pricing; Economic models; Financial markets; Labour markets; Market structure and pricing